PMSM Speed Control using SVPWM Technique - Rajasekar, S.; Supriya, M.; Naresh, P.; Devaraj, R.; Kavya, J. (Journal of Electronics and Informatics, 2023)
A simulation analysis of a voltage source inverter using Space Vector Pulse Width Modulation (SVPWM) to control the speed of a Permanent Magnet Synchronous Motor (PMSM) has been presented in this research. PMSM is an AC drive that widely helps in high power propulsion systems. SVPWM is one of the best PWM techniques. The SVPWM is powered by a voltage source inverter connected to the PMSM. Space vector modulation is responsible for developing pulses to control the switches of the inverter. This research introduces an SVPWM-fed three-phase voltage source inverter for controlling the speed of PMSM drives using MATLAB/Simulink.
Keywords: Space Vector Pulse Width Modulation; Voltage Source Inverter; Permanent Magnet Synchronous Motor